Manfaat Penggunaan Buku Penghubungsebagai Media Komunikasi Guru Dengan Orang Tuasiswa Kelas IIA SD Muhammadiyah 3 Nusukan Surakarta - Rahmawati, Indah, Honest Ummi Kaltsum, S.S. M.Hum (2017)
This research is aimed to describe 1)using connecting books and 2) the benefit ofusing connecting books as communication media between teacher and parents of IIA elementary students of 3 MuhammadiyahNusukan, Surakarta. This research is a qualitative research with analytic descriptive approach. The collecting data techniques used are interview, observation, and documentation. Data validity was checked using triangulation method and source triangulation. The data analysis technique used is interactive analysis technique which consist of data reduction, data explanation, and conclusion & verification. Based on the research result, can be concluded that 1) using connecting books are a) tools or means of teachers' communication mediator to parents, b) to deliver messages such as assignments, announcement, information, and students' condition, c) The format of connecting books consists, d) using by teacher, students, and their parents. 2) The benefits of the connecting books are a) as a communication media, b) deliver message, c) easy and fast communication, d) know the students' condition, e) train discipline attitude and writing ability, and f) bring more spirit to communicate.